Moss and Adams heart disease in infants, children, and adolescents : including the fetus and young adult. Volume II - Allen, Hugh D. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
"Established since 1968 as a classic pediatric cardiology text, this edition uses new technology to bring the most sought after information in the most concise, effective manner. This eighth edition is reduced from the two-volume work into a concise, easy-to-use single volume moving all but key references to the online component. Leading international experts describe state-of-the-art diagnostic and interventional techniques for treatment of young patients with congenital and acquired heart diseases and for adult survivors of congenital heart disease"--